Scaling up production of recombinant human basic fibroblast growth factor in an Escherichia coli BL21(DE3) plysS strain and evaluation of its pro-wound healing efficacy - Li, Le; Yu, Bingjie; Lai, Yingji; Shen, Siyuan; Yan, Yawei; Dong, Guojun; Gao, Xiangyun; Cao, Yanrong; Ge, Caojie; Zhu, Liqin; Liu, Huan; Tao, Shanhui; et al. (Frontiers in Pharmacology, 2024)
In this study, the synthetic DNA sequence of human bFGF was successfully cloned into a mpET-3c vector containing a kanamycin resistance gene and then inserted into Escherichia coli BL21(DE3) plysS strain. To optimize the production yield of the target protein, various fermentation parameters were systematically optimized by BOX-Behnken design. The optimized fermentation conditions were further validated and successfully implemented in large-scale fermentation (500-L). Consequently, an impressive bacterial yield of 46.8 ± 0.3 g/L culture with an expression level of hbFGF reaching 28.2 ± 0.2% was achieved. In addition, a three-step purification protocol involving CM-Sepharose, heparin affinity, and SP-Sepharose column chromatography was developed to separate and purify the hbFGF protein. The final yield of the purified protein was 114.6 ± 5.9 mg/L culture with RP-HPLC, SEC-HPLC, and SDS-PAGE purity exceeding 98%. Isoelectric focusing electrophoresis, MALDI-TOF/MS analysis, amino acid sequencing, CD spectroscopy, and western blotting were performed to further authenticate its identity. Furthermore, the purified hbFGF exhibited a specific activity of 1.05 ± 0.94 × 106 AU/mg and significantly enhanced wound healing in a deep second-degree scald wound diabetic rat model. This established large-scale production process for hbFGF demonstrates stability and time efficiency while providing a solid foundation for future industrial production.